READING HABITS IN THE DIGITAL AGE: CHANGES TREND AND BEHAVIOR IN ALPHA GENERATION - Azzahra Egadwi Miranda; Hermansyah Hermansyah; Asti Veto Mortini (Universitas PGRI Palembang, 2023)
This thesis was concerned with the Reading Habits In The Digital Age: Changes Trend and Behavior in Alpha Generation. The problem of this research was how could trends and behaviors in alpha generation change reading habits. The purpose of this study is to identify whether the alpha generation has the habit of reading in the digital age. The objective of this research was generation alpha especially students of Junior High School 11 Palembang, Seventh-grade. Based on the data taken from the students choose the answer based on their honest opinion. There were (13%) Fully Agree and (50%) Agree of 30 students were agree on reading habits and the use of technology for reading habits. And (4%) Highly Disagree and (33%) Disagree about reading habits and the use of technology so here the comparison was quite comparable to the reading habits of students using technology in this digital age. It could be can be concluded that the alpha generation has a habit of reading using technology that is included in the digital age such as using a handphone or laptop and reading habits have reading behavior in students.